Analisis Kandungan Formalin pada Ikan Nila (Oreochromis niloticus) yang Dijual di Pasar Tradisional Kota Gorontalo - Sri Gita Tamai,; Tusaban Tusaban,; Dewi Shinta Achmad,; Nur Jihan Fareranty Piu, (Student Scientific Creativity Journal, 2026)
Food safety of fresh fish is an important concern because fish is highly perishable and may be misused with hazardous preservatives such as formalin. This study aimed to determine formalin content and analyze the relationship between length and weight of Nile tilapia (Oreochromis niloticus) and formalin levels in traditional markets of Gorontalo City. The study was conducted from January to February 2026 in five traditional markets, namely TPI Tenda, Moodu, Potanga, Andalas, and Sentral. Nile tilapia samples were analyzed using a formaldehyde test kit, and formalin levels were expressed in ppm. Total length and fish weight were measured, and the relationship between physical size and formalin content was analyzed using Pearson correlation. The results showed that all Nile tilapia samples tested positive for formalin, with concentrations ranging from 0.11 to 0.23 ppm. The highest formalin levels were found in TPI Tenda and Moodu, each at 0.23 ppm, while the lowest level was found in Sentral at 0.11 ppm. Fish length ranged from 19.43 to 25.61 cm, while fish weight ranged from 0.17 to 1.78 g. The correlations between length and formalin content and between weight and formalin content were both very strongly negative, with r = -0.97. These findings indicate that smaller fish tended to contain higher formalin levels. Market supervision, trader education, and formalin-free fish handling practices should be strengthened to protect consumer health.